2016
DOI: 10.1021/acs.joc.6b02578
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Branched Tryptamines via the Domino Cloke–Stevens/Grandberg Rearrangement

Abstract: The rearrangement of cyclopropylketone arylhydrazones generated in situ from arylhydrazine hydrochlorides and ketones leads to formation of tryptamine derivatives. The use of (2-arylcyclopropyl)ethanones in the reactions with model 4-bromophenylhydrazine hydrochloride gives branched tryptamines with aryl groups in the α-position to the amino group, while (2-methylcyclopropyl)ethanone gives a mixture of α- and β-substituted products in a ratio of 1:3. The method was found effective in the synthesis of enantiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As shown in Scheme , ethyl-2-aminopyrimidine-5-carboxylate ( 21 ) on reaction with 17o in the presence of palladium­(II) acetate gave intermediate 22 , which on hydrolysis afforded acid precursor 23 . Requisite amines 7a – e (Supporting Information (SI), Figure 1) were synthesized using the known methods, , and they were individually coupled with 23 in the presence of DMAP and EDCI·HCl at 50 °C to furnish the final products 24a – e (Scheme ). Similarly, compound 24f was synthesized using acid 23 and 2-trifluroindole-3-ethanolamine ( 7f ), which was in turn prepared form 2-vinyl-pyrrolidin-2-one (SI Figure 1).…”
Section: Results and Discussionmentioning
confidence: 99%
“…As shown in Scheme , ethyl-2-aminopyrimidine-5-carboxylate ( 21 ) on reaction with 17o in the presence of palladium­(II) acetate gave intermediate 22 , which on hydrolysis afforded acid precursor 23 . Requisite amines 7a – e (Supporting Information (SI), Figure 1) were synthesized using the known methods, , and they were individually coupled with 23 in the presence of DMAP and EDCI·HCl at 50 °C to furnish the final products 24a – e (Scheme ). Similarly, compound 24f was synthesized using acid 23 and 2-trifluroindole-3-ethanolamine ( 7f ), which was in turn prepared form 2-vinyl-pyrrolidin-2-one (SI Figure 1).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In particular, Cloke–Wilson rearrangement of cyclopropyl carbonyls and imines, cyclopropanecarboxylate lactonization, and related processes can produce five-membered heterocycles . The homo-Nazarov rearrangement and related reactions can form six-membered rings . Formation of seven-membered cycles is also known .…”
Section: Introductionmentioning
confidence: 99%
“…In 1987, Robinson et al documented that, in the presence of dry HCl in refluxing methanol, cyclopropyl ketone and phenyl hydrazine react to afford a mixture of 1,3-diphenyl-1,4,5,6-tetrahydropyridazine (26% yield) and 2-phenyl-3-(2-chloroethyl) indole (17% yield) . Following these reports, Tomilov et al demonstrated two complementary reaction conditions, in refluxing acetonitrile, cyclopropyl ketone and phenyl hydrazine hydrochloride react to produce tryptamines as the major product along with the formation of a trace amount of tetrahydropyridazine, whereas, in the presence of NH 4 I at reflux in acetonitrile, cyclopropyl ketone and phenyl hydrazine hydrochloride react to furnish a mixture of tetrahydropyridazine and tryptamine . In the second case, the product ratio varies from substrate to substrate; in some cases, tetrahydropyridazine became the major product, and in some instances, tryptamines were produced as the primary product.…”
Section: Introductionmentioning
confidence: 99%